The Organisation for Economic Co-operation and Development's International Early Learning and Child Well-being Study: The scores are in!. (June 2020) - Moss, Peter; Urban, Mathias
This is the fourth colloquium for Contemporary Issues in Early Childhood on the Organisation for Economic Co-operation and Development's International Early Learning and Child Well-being Study, and marks the recent publication by the Organisation for Economic Co-operation and Development of reports on the first round of this study. In it, the authors discuss what the results tell us, what they do not and what might come next. They conclude by supporting the need for comparative studies of early childhood education, but argue that the International Early Learning and Child Well-being Study is not the way to go.